Youth and brackish water cage culture industry: a recipe for success - Idris, Khairuddin; Mohamed Shaffril, Hayrol Azril; Raja Omar, Raja Zainuddin; Hamzah, Azimi; Man, Norsida; Alby, Jeffrey Lawrence D'Silva (Universiti Putra Malaysia Press, 2013)
The aquaculture industry plays an important role in strengthening the socio-economic aspects of the community in providing job- and income-generating opportunities. The Brackish Water Cage Culture has been identified as one of the potential enterprises within the aquaculture industry that can aid in this. The involvement of youth in this industry is important to ensure the industry’s success. This industry may also effectively help to solve the problem of unemployment, especially among youth. The main objective of this paper is to discover the potential benefits and problems faced by youth in the brackish water cage culture industry. Literature and document analyses provide the data in this qualitative study. Findings from this study revealed a number of potential benefits from this industry, which includes business and employment opportunities. This paper also highlights several potential problems and discusses issues related to capital and competitiveness in the industry. This paper goes on to suggest a number of recommendations that the authorities can consider to further develop this industry.